Effects of Using Air Curtains on Energy Consumption During Cooling Season Under Different Climate Conditions - Erdem, Serkan; Onan, Cenk (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
In zones separated by doors with many entrances and exits, it is crucial in terms of energy consumption to protect the conditioned air in the indoor environment from the effects of outside air. The increase in door dimensions and opening frequency make this effect even more evident. Various methods are used to prevent leakage of outside air into the indoor environment. In this study, we investigated the effects of using air curtains on energy consumption during the cooling season in a factory building. The door width and height in this building, which has a high story height, were also large. These 26 doors must remain open all the time because of the production process. With a transient model developed on Transient System Simulation Tool (TRNSYS) coupled with Contaminant Transport Analysis Software (CONTAM), we showed the effects of using the air curtains in different climate conditions. As a result, we demonstrated that using air curtains will provide great savings, especially in cities with high cooling requirements.
Keywords: Air curtain; building simulation; energy efficiency; modeling; FLOW; INFILTRATION; SAVINGS; HEAT; Thermodynamics